Strength and durability performance of cement-treated Tullahan River dredged material with fly ash - Cabalagnan, Zarah Christine P.; Chua, Christian C.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Dredged materials are considered as a waste in the country and in order to cut the cost of the current disposal methods, studies can be done to utilize these materials as a resource. This study evaluated the strength and durability performance of cement-treated Tullahan River dredged material with fly-ash. Type I Portland Cement at varying concentrations (5%, 7%, 9%) and Class F pozzolanic fly-ash at varying concentrations (0%, 15%, 25%) were used in the study. The leaching potential of the dredged material was also investigated and results showed that minimal to negligible leaching may occur except for the heavy metal Mercury. The compressive strength obtained were then compared to standards to determine the suitability of the material as a road base course, road subbase course and structural fill. Overall, the compressive strength of most of the test cases were not able to meet the standards for its intended alternative application. The reason for this is the type of soil and the organic matter content which is relatively high for these applications.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Dredging spoil; River sediments -- Testing